ANALISIS HUKUM TERHADAP HAK PARTAI POLITIK DALAM MENGUSUNG CALON PRESIDEN - Sonia Surya Hanim Lubis; A.A Gde Putra Arjawa; I Nyoman Suandika (Yayasan Nusantara Hasana Berdikari, 2024)
This research aims to describe the legal analysis of the rights of political parties in nominating presidential candidates. Political parties are a manifestation of people's freedom to form groups according to their interests. This research is normative legal research, and uses qualitative descriptive analysis. The results of this research indicate that the requirements for the nomination of President and Vice President are in accordance with the provisions of Article 222 of the Law of the Republic of Indonesia Number 7 of 2017 which regulates the threshold provisions for President and Vice President candidates, namely Political Parties or Associations of Election Contesting Political Parties that meet the requirements for obtaining seats of at least 20% (twenty percent) of the total number of DPR seats or obtaining 25% (twenty five percent) of valid votes nationally in the previous DPR member election. The provisions for the nomination mechanism for President and Vice President are regulated in the 1945 Constitution and Law Number 42 of 2008 concerning the Election of the President and Vice President. Political parties or combinations of political parties can only nominate 1 (one) pair of candidates in accordance with the internal mechanisms of political parties and/or joint deliberations of political parties which are held democratically and openly. This is regulated in Article 221 – Article 223 of Law Number 7 of 2017.